Hubungan Dukungan Keluarga dengan Kepatuhan Minum Obat Pada Pasien Tuberkulosis Di Wilayah Puskesmas Rowosari I - Dhianisa, Sofy Mila; Nutrisia Nu’im Haiya; Abrori; Iskim Luthfa (An-Najat, 2025)
: The success of treatment for Tuberculosis patients is greatly influenced by fulfilling the complete medication regimen to completion. Family support is very necessary to encourage patients to adhere to treatment. This research uses a quantitative descriptive analytical method involving 32 respondents selected through total sampling technique. The criteria include outpatients at the Rowosari I Community Health Center who are undergoing the advanced stage, intensive stage, live with their families, and are willing to fill out a questionnaire. Medication adherence surveys (MMAS) and family support questionnaires (Nursalam, 2016) are among the tools utilized. The Spearman Rho test was used for analysis, and the findings showed that r = 0.886 and p = 0.000. According to the research, the majority of the study's respondents were male, elderly, and had completed secondary school. According to the findings, individuals who had less family support were more likely to not take their medications as prescribed. Respondents who fell into the adequate group for family assistance, however, expressed some degree of happiness. Respondents who have strong family support are more likely to take their medications as prescribed. There is a strong correlation between medication compliance and family support.